2019
DOI: 10.30650/jik.v7i1.243
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Nurses Age and Compliance in the Implementation of Prevention of Falling Patients in the General Hospital of the Samarinda Government

Abstract: In the patient safety standards / International Patient Safety Goal (IPSG), especially the prevention of the risk of falling must be applied by nurses, age is one of the internal factors that affect compliance. This study aims to determine the correlation between age of nurses with adherence in the implementation of prevention of falling patients in Samarinda Government Hospital using a descriptive correlation design and cross sectional approach. The instrument used in this study was a questionnaire and observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
0
1
Order By: Relevance
“…It was not much different when it compared to young nurses who are less than 30 years old. The result of this study was different from the previous study conducted by Safrudin & Milkhatun (2019) who found that there was a significant relationship between the nurse's age with the compliance in implementing patient safety in the hospital.…”
Section: Discussioncontrasting
confidence: 99%
“…It was not much different when it compared to young nurses who are less than 30 years old. The result of this study was different from the previous study conducted by Safrudin & Milkhatun (2019) who found that there was a significant relationship between the nurse's age with the compliance in implementing patient safety in the hospital.…”
Section: Discussioncontrasting
confidence: 99%